2001
DOI: 10.1111/j.1365-2621.2001.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of UV‐C irradiation to prevent decay and maintain postharvest quality of ripe ‘Tommy Atkins’ mangoes

Abstract: Ripe mangoes`Tommy Atkins' were exposed to UV-C irradiation for 10 and 20 min, prior to storage for 14 days at 5 or 20°C and a shelf-life period of 7 days at 20°C. UV-C-treated fruit maintained better visual appearance than unirradiated controls. UV-C irradiation for 10 min was the most eective regime in suppressing decay symptoms and maintaining ®rmness during storage at 5 or 20°C. Such fruit (treated with UV-C for 10 min) showed greater levels of putrescine and spermidine after cold storage than controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 19 publications
6
40
0
9
Order By: Relevance
“…UV-C illumination as a postharvest treatment has proven to be beneficial in delaying postharvest fruit senescence and reducing decay in various fruits and vegetables (Allende & Artes, 2003;Erkan, Wang, & Wang, 2008;Gonzalez-Aguilar, Wang, Buta, & Krizek, 2001). A previous study (Perkins-Veazie, Collins, & Howard, 2007) has indicated that postharvest application of UV-C might be effective in stimulating the antioxidant content of blueberries.…”
Section: Introductionmentioning
confidence: 95%
“…UV-C illumination as a postharvest treatment has proven to be beneficial in delaying postharvest fruit senescence and reducing decay in various fruits and vegetables (Allende & Artes, 2003;Erkan, Wang, & Wang, 2008;Gonzalez-Aguilar, Wang, Buta, & Krizek, 2001). A previous study (Perkins-Veazie, Collins, & Howard, 2007) has indicated that postharvest application of UV-C might be effective in stimulating the antioxidant content of blueberries.…”
Section: Introductionmentioning
confidence: 95%
“…Exposure to low UV-C doses delayed ripening, chlorophyll degradation and senescence of fresh produce, such as apples (Hemmaty et al, 2007), tomatoes (Obande et al, 2011), broccoli (Costa et al, 2006), strawberries (Pombo et al, 2009) and mangoes (Gonzalez-Aguilar et al, 2001. Gonzalez-Aguilar et al (2001 reported that UV-C treatment helped to improve the postharvest quality of 'Haden' mango and ripe 'Tommy Atkins' mangoes, and suppressed decay symptoms. In our previous studies, UV-C applied at 6.16 kJ m À2 reduced anthracnose disease in mango cv.…”
Section: Introductionmentioning
confidence: 98%
“…It does not require chemicals or heat, and is not expensive. Presently, UV radiation technology is used as an alternative to chemical sterilization in food products (Lamikanra, Kueneman, Ukuku, & Bett-Garber, 2005), and UV-C (wavelength of 220-300 nm with 90% of emission at 253.7 nm) has been approved by the FDA for use on food products to control surface microorganisms (US Food, 2007 Within the UV-C range, inactivation studies using the 253.7 nm light energy have been shown to be effective in reducing pathogenic bacteria and spores in vegetables (Allende & Artés, 2003) and fruits (González-Aguilar, Wang, Buta, & Krizek, 2001). However, few studies have been conducted on the application of UV-C irradiation to chicken products.…”
Section: Introductionmentioning
confidence: 99%